Introduction to mass communication - Baran, Stanley J. (McGraw-Hill, 2012)
This text encourages students to be active media consumers and gives them a deeper understanding of the role that the media play in both shaping and reflecting culture. Through this cultural perspective, students learn that audience members are as much a part of the mass communication process as are the media producers, technologies, and industries. This was the first, and remains the only, university-level text to make media literacy central to its approach, and given recent national and global turmoil, its emphasis on media use and democracy could not be more timely